The Middle East in the shadow of Afghanistan and Iraq - Larrabee, F. Stephen (Conference proceedings (Rand Corporation), 2003)
On May 5-6, 2003, RAND and the Geneva Centre for Security Policy held a two-day conference in Geneva that examined the impact of the Iraq war on the security of the Middle East. It was attended by specialists from the United States, Europe, and the Middle East. This document summarizes the main issues and points of discussion at the conference: the impact of Iraq on the war on terrorism; the future of Iran and Iraq, repercussions of the war on Syria, the Levant, Turkey, Jordan, and the Arabian peninsula; and the effect of the war on transatlantic ties.